2018
DOI: 10.3390/ma11061031
|View full text |Cite|
|
Sign up to set email alerts
|

Properties of Experimental Dental Composites Containing Antibacterial Silver-Releasing Filler

Abstract: Secondary caries is one of the important issues related to using dental composite restorations. Effective prevention of cariogenic bacteria survival may reduce this problem. The aim of this study was to evaluate the antibacterial activity and physical properties of composite materials with silver sodium hydrogen zirconium phosphate (SSHZP). The antibacterial filler was introduced at concentrations of 1%, 4%, 7%, 10%, 13%, and 16% (w/w) into model composite material consisting of methacrylate monomers and silan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 128 publications
3
44
0
Order By: Relevance
“…In the previously published part [37], the antimicrobial properties were confirmed via three-month in vitro experiments; thus, further tests were needed to investigate the other properties of the obtained composites related to their application. Additionally, S-P has also been investigated in our other works as an additive into silicone soft lining material [53] and direct restorative photopolymerizable resin-based composites [54], where only a slight influence of the filler on some physicochemical properties was noted. However, for the currently tested composites, the matrix and the method of introducing the filler into it were different which determined the inhomogeneous morphology of polymerized composites related with the used components (PMMA pre-polymerized particles) [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously published part [37], the antimicrobial properties were confirmed via three-month in vitro experiments; thus, further tests were needed to investigate the other properties of the obtained composites related to their application. Additionally, S-P has also been investigated in our other works as an additive into silicone soft lining material [53] and direct restorative photopolymerizable resin-based composites [54], where only a slight influence of the filler on some physicochemical properties was noted. However, for the currently tested composites, the matrix and the method of introducing the filler into it were different which determined the inhomogeneous morphology of polymerized composites related with the used components (PMMA pre-polymerized particles) [37].…”
Section: Discussionmentioning
confidence: 99%
“…Chromatography techniques can be used to determine the release of compounds such as the residual monomer or dibenzoyl peroxide [121-123]. These investigations can be considered for selected composites together with analyses for other materials filled with S-P and based on different matrixes [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the bactericidal effect of chlorhexidine was not affected even in the presence of human organic substances. In addition, composites containing silver nanoparticles, which was considered to be a broad‐spectrum antibacterial agent, exhibited a potent antibacterial activity . Silver nanoparticles will contact with the cell membrane of bacteria and form obvious irregular perforation on the cell membrane, resulting in changes and degradation of the membrane system structure, leading to bacteria death .…”
Section: Strategies To Address Challenges Facing Dental Compositesmentioning
confidence: 99%
“…Different approaches have been adopted to improve the quality and performance of these composites [20][21][22]. One of these is the development of fillers that can release substances with antibacterial effects or buffer the acids produced by bacteria [23][24][25][26]. Fluorine-containing filler particles have been introduced in order to eliminate the cariostatic demineralization effect produced by the filling restoration.…”
Section: Introductionmentioning
confidence: 99%